2022
DOI: 10.3390/nu14112253
|View full text |Cite
|
Sign up to set email alerts
|

Intakes of Folate, Vitamin B6, and Vitamin B12 in Relation to All-Cause and Cause-Specific Mortality: A National Population-Based Cohort

Abstract: The evidence regarding the intake of dietary folate, vitamin B6, and vitamin B12 in relation to mortality in the general population is limited. This study aimed to examine the relationship between dietary intakes of folate, vitamin B6, and vitamin B12 in relation to all-cause and cause-specific mortality in a large U.S. cohort. This study included a total of 55,569 adults from the Third National Health and Nutrition Examination Survey (NHANES III) and NHANES 1999–2014. Vital data were determined by linking wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…A summary of findings from seven studies [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ] examining the relationship between B6 status and all-cause mortality in the general population is presented in Table 3 . Among these seven studies, six [ 23 , 24 , 25 , 26 , 27 , 28 ] indicated a significant inverse association between B6 status and all-cause mortality.…”
Section: Epidemiological Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A summary of findings from seven studies [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ] examining the relationship between B6 status and all-cause mortality in the general population is presented in Table 3 . Among these seven studies, six [ 23 , 24 , 25 , 26 , 27 , 28 ] indicated a significant inverse association between B6 status and all-cause mortality.…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…A summary of findings from seven studies [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ] examining the relationship between B6 status and all-cause mortality in the general population is presented in Table 3 . Among these seven studies, six [ 23 , 24 , 25 , 26 , 27 , 28 ] indicated a significant inverse association between B6 status and all-cause mortality. A study by Cui et al [ 22 ] did not indicate results for all-cause mortality, although their study indicated that B6 intake was significantly associated with a lower mortality risk from heart failure.…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…Evidence among general adults is scares. Furthermore, although studies based on similar data have found that folate, vitamin B6 or vitamin B12 have an effect on death and high blood pressure, their effect on cardiovascular disease is unclear (27)(28)(29). Therefore, we investigated the association of dietary folate, vitamin B6, and vitamin B12 with the prevalence of CVD in a cross-sectional study of the general United States adult population using data from the National Health and Nutrition Examination Survey (NHANES).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, its relationship with mortality has not been investigated, unlike other vitamin B family members. For example, data from the Third National Health and Nutrition Examination Survey (NHANESIII) and NHANES 1999-2014 showed higher dietary folate intake reduced all-cause mortality, and CVD mortality by 23% (hazard ratio (HR): 0.77, 95% CI 0.71-0.85) and 41% (HR: 0.59, 95% CI 0.48-0.72) in men and by 14% and 47% in women, respectively [17]. Among participants with a high risk of CVD, a folate supplement reduced the CVD mortality by 44% and all-cause mortality by 28% [18].…”
Section: Introductionmentioning
confidence: 99%